Hybrid TaON/LaTiO2N photoelectrode for water oxidation. Issue 3 (22nd February 2020) - An, Pengda; Yang, Baopeng; Zhang, Ning; Li, Hongmei; Liu, Min
Abstract: Efficient and stable photoelectrodes for water oxidation are highly desirable in the field of photoelectrochemical (PEC) water splitting. However, photoelectrodes with low externally applied bias usually exhibit weak photocurrent and vice versa. Herein, novel and efficient CoOx -TaON/LTON composite photoanodes have been successfully prepared by a microwave assisted method followed with a particle transfer procedure. The obtained photoanode generated an anodic photocurrent of 7.2 mA cm −2 at 1.2 VRHE and initiated the anodic photourrent at 0.5 VRHE . The HC-STH of the composite photoelectrode reached 1.0% at 1.2 VRHE . Further, stoichiometric oxygen and hydrogen are stably produced on the photoanode and the counter electrode with a Faraday efficiency of unity for 2 h.